Pendampingan Pengembangan Unit Usaha Badan Usaha Milik Desa (BUMDes) di Desa Padangan Kecamatan Ngantru Kabupaten Tulungagung - Ahmad Syaickhu; Purwanto Purwanto (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to strengthen institutional capacity and develop the business units of the Padangan Village-Owned Enterprise (BUMDes) through enhanced managerial capabilities, business innovation, and enhanced digital marketing strategies tailored to local potential and needs. The program was implemented using a participatory empowerment approach involving various stakeholders, including the village government and local economic actors. The methods used included needs assessment, management and entrepreneurship training, intensive mentoring, and collaborative business planning. The program's results demonstrated significant improvements in BUMDes organizational governance, administrative professionalism, and a more organized and accountable financial reporting system. Furthermore, business unit diversification, local product quality improvement, and community capacity to utilize digital technology for marketing activities increased. The program also provided academic contributions in the form of empirical data and an applicable model of village empowerment based on Islamic economics. Overall, empowerment based on participation and Islamic economic values ​​has been proven to promote sustainable village economic resilience and independence.